Six minutes to promote change: People, not facts, alter students' perceptions on climate change. Issue 11 (1st May 2021) - Sauer, Kodiak A.; Capps, Daniel K.; Jackson, David F.; Capps, Krista A.
Abstract: Anthropogenic climate change threatens the structure and function of ecosystems throughout the globe, but many people are still skeptical of its existence. Traditional "knowledge deficit model" thinking has suggested that providing the public with more facts about climate change will assuage skepticism. However, presenting evidence contrary to prior beliefs can have the opposite effect and result in a strengthening of previously held beliefs, a phenomenon known as biased assimilation or a backfire effect. Given this, strategies for effectively communicating about socioscientific issues that are politically controversial need to be thoroughly investigated. We randomly assigned 184 undergraduates from an environmental science class to one of three experimental conditions in which we exposed them to short videos that employed different messaging strategies: (a) an engaging science lecture, (b) consensus messaging, and (c) elite cues. We measured changes in student perceptions of climate change across five constructs (content knowledge, acceptance of scientific consensus, perceived risk, support for action, and climate identity) before and after viewing videos. Consensus messaging outperformed the other two conditions in increasing student acceptance of the scientific consensus, perceived risk of climate change, and climate identity, suggesting this may be an effective strategy for communicating the gravity of anthropogenic climate change. Elite cues outperformed the engaging science lecture condition in increasing student support for action on climate, with politically conservative students driving this relationship, suggesting that the messenger is more important than the message if changing opinions about the necessity of action on climate change is the desired outcome. Relative to the other conditions, the engaging science lecture did not support change in students' perceptions on climate, but appealing to student respect for authority produced positive results. Notably, we observed no decline in students' acceptance of climate science, indicating that none of the conditions induced a backfire effect. Abstract : University educators are required to teach socially and politically controversial concepts to students from a wide range of political backgrounds. At the same time, university professors are increasingly more politically liberal and less religious than the general population. Therefore, it can be challenging for professors to effectively convey information about topics that are socially and politically controversial to diverse groups of students. This study sought to evaluate the effectiveness of video‐based teaching strategies to support student acceptance of global, anthropogenic climate change.